Rust and drought effects on gene expression and phytohormone concentration in big bluestem - Frank, Erin (Kansas State University, 2007)
While plants are typically exposed to multiple stressors in the field, studies of genome-wide gene expression and phytohormone responses in wild plant species exposed to multiple stressors are rare. Our objectives were to determine the effects of drought and rust stress on gene expression in Andropogon gerardii, the dominant grass in tallgrass prairie, and associated levels of phytohormone production. In a factorial design, plants experiencing drought or non-drought conditions were either inoculated with the rust pathogen Puccinia andropogonis or not inoculated. Gene expression was evaluated with maize microarrays. Drought-stressed plants significantly decreased expression of genes associated with photosynthesis and the hypersensitive response, while expression of genes associated with chaperones and heat-shock proteins increased. No significant differences in gene expression in response to the rust treatment were detected using a mixed model analysis of variance and false discovery rate protection, probably because of the low infection rate. Phytohormone production increased when both stresses were present. The rust treatment significantly increased benzoic acid (BA) production in the presence of drought, while the drought treatment alone significantly increased salicylic acid (SA) production. Leaf tips usually had higher levels of all phytohormones in all treatments and the leaf section evaluated had a larger effect on phytohormone level than did the treatments applied.
Keywords: Andropogon gerardii; Puccinia andropogonis; Gene expression; Salicylic acid; Jasmonic acid; Drought; Agriculture, Plant Pathology (0480)